Inclusive assessment in primary school: addressing diversity and freedom - Saadet Garan (IUL Research)
This study focuses on how primary school teachers evaluate inclusive education as a way to include all children in schools, which is a problem in education systems around the world. A phenomenology design, one of the qualitative research patterns, was used in the study. The study group consists of 11 primary school teachers with disadvantaged students in their classes in Istanbul. According to the information obtained, teachers stated that they did not take inclusivity/multiculturalism education courses at the Faculty of Education; therefore, they did not consider themselves sufficient, the materials necessary for inclusive education in their classrooms were not sufficient, they did not devote enough time to students with differences due to the large number of students in their classes, they could not cooperate with families. Since the findings are obtained from the experiences of teachers working in the field, they can contribute to all other teachers and to the literature and educational program designers.